Focus on The Correctness of Results: Factors Contributing to Invisible Thinking Processes in High-Resilience Mathematical Students - Faiqatul ‘Athiyah; Abdur Rahman As’ari; Erry Hidayanto (Jurnal Pendidikan Sains, 2023)
The cognitive process of thinking plays a pivotal role in understanding one's surroundings and effectively solving problems. This research endeavors to delve into the intricate factors contributing to the concealment of thinking processes in writing among students with high mathematical resilience. Employing a qualitative approach, specifically adopting a case study research design, the study concentrates on the students enrolled at SMPI Al-Lailiyah Sumenep. The comprehensive dataset is derived from the results of numeracy-type tests and interviews conducted with the student. The outcomes of this research shed light on a persistent challenge observed during the problem-solving phase among students exhibiting high mathematical resilience. A predominant tendency is noted, wherein these students habitually prioritize the correctness of final results over conveying the step-by-step reasoning behind their solutions. Several causative factors contribute to this phenomenon. First, the students’ established approach to problem-solving, emphasizing the end result, impedes the transparent expression of their cognitive processes in writing. Additionally, past experiences related to the types of questions posed, the depth of their understanding of mathematical concepts, a lack of feedback from teachers, and the absence of visible thinking routines in written assignments during the learning process collectively contribute to the challenge.DOI: 10.17977/jps.v11i32023p079